Scaling up housing services within the child welfare system: policy insights from simulation modeling - Fowler, Patrick J. (Child maltreatment, 2020)
Objectives: Housing insecurity and homelessness contribute to risk of maltreatment among one in five of the nearly 3.5 million children annually investigated for maltreatment in the United States. The Family Unification Program (FUP) - a federal initiative - connects inadequately housed families involved in child welfare with long-term rental subsidies to avoid foster placement. However, FUP remains understudied and underutilized with funding levels that serve only a fraction of eligible households. The present study uses system dynamics modeling to inform decision-making by testing policies for scaling FUP. Method: Simulations model delivery of FUP within child welfare from a feedback perspective. Calibrated on national data, models replicate trends in child welfare involvement from 2013 through 2016, and analyses forecast rates through 2019. Experiments test policies that enhance FUP. Outcomes track system-wide rates of family separation and returns on investment of expanded housing interventions. Results: Dramatic expansions of FUP benefit more families and improve marginal return on investment. Yet, scale-up fails to reduce system-wide rates of family separation or generates substantial cost-savings. Conclusions: Simulations demonstrate structural challenges for scaling FUP. Constant demand for affordable housing constrains sustainable improvements in child protection. Child welfare responses to homelessness require innovations that reduce demand for housing services through prevention and earlier intervention.